New Perspectives on Technology, Values, and Ethics
XIV, 219 p.
Keywords: This book focuses on a key issue today: the role of values in technology, with special emphasis on ethical values. This topic involves the analysis of internal values in technology (as they affect objectives, processes, and outcomes) and the study of external values in technology (social, cultural, economic, ecological, etc.). These values — internal and external — are crucial to the decision making of engineers. In addition, they have increasing relevance for citizens concerned with the present and future state of technology, which gives society a leading position in technological issues. The book follows three main lines of research: 1) new perspectives on technology, values, and ethics; 2) rationality and responsibility in technology; and 3) technology and risks. This volume analyzes the two main sides involved here: the theoretical basis for the role of values in technology and a practical discussion on how to implement them in our society. Thus, the book is of interest for philosophers, engineers, academics of different fields, and policy-makers. The style used lends itself to broad audience.